Cerebral Theta-Burst Stimulation Combined with Physiotherapy in Patients with Incomplete Spinal Cord Injury: A Pilot Randomized Controlled Trial - Xiaojun Feng; Tingting Wang; Yan Jiang; Yi Liu; Haifeng Yang; Zongyu Duan; Leilei Ji; Juan Wei (Medical Journals Sweden, 2023)
Objective: To measure the effects of cerebral intermittent theta-burst stimulation with physiotherapy on lower extremity motor recovery in patients with incomplete spinal cord injury. Design: Randomized, double-blinded, sham-controlled trial. Subjects: Adults with incomplete spinal cord injury. Methods: A total of 38 patients with incomplete spinal cord injury were randomized into either an intermittent theta-burst stimulation or a sham group. Both groups participated in physiotherapy 5 times per week for 9 weeks, and cerebral intermittent theta-burst stimulation or sham intermittent theta-burst stimulation was performed daily, immediately before physiotherapy. The primary outcomes were lower extremity motor score (LEMS), root-mean square (RMS), RMS of the quadriceps femoris muscle, walking speed (WS), and stride length (SL). Secondary outcomes comprised Holden Walking Ability Scale (HWAS) and modified Barthel Index (MBI). The outcomes were assessed before the intervention and 9 weeks after the start of the intervention. Results: Nine weeks of cerebral intermittent theta-burst stimulation with physiotherapy intervention resulted in improved recovery of lower extremity motor recovery in patients with incomplete spinal cord injury. Compared with baseline, the changes in LEMS, WS, SL, RMS, HWAS, and MBI were significant in both groups after intervention. The LEMS, WS, SL, RMS, HWAS, and MBI scores were improved more in the intermittent theta-burst stimulation group than in the sham group. Conclusion: Cerebral intermittent theta-burst stimulation with physiotherapy promotes lower extremity motor recovery in patients with incomplete spinal cord injury. However, this study included a small sample size and lacked a comparison of the treatment effects of multiple stimulation modes, the further research will be required in the future. LAY ABSTRACT Spinal cord injury is a serious condition caused by spinal trauma and tumours. Improving the patient's limb function during recovery poses an important challenge. Transcranial magnetic stimulation technology is a new treatment used to improve nervous system function, which has shown promising results in treating spinal cord injuries in recent years. However, the effect of a specific type of magnetic stimulation, cerebral intermittent theta-burst stimulation, with routine physical therapy on lower extremity motor recovery in patients with incomplete spinal cord injury has not yet been explored. The results of this study suggest that 9 weeks of brain intermittent theta-burst stimulation combined with physical therapy has a positive short-term effect on lower extremity movement and recovery of daily living ability in patients with incomplete spinal cord injury, which might provide new insight into motor rehabilitation for spinal cord injury.